Clinical Symptoms Used for Screening Diabetic Populations with Family History of Type 2 Diabetes Mellitus - Siti Marlina; I Dewa Putu Pramantara; Hari J. Kusnanto; Mark Alan Graber (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2018)
Background: The annual prevalence of diabetes is increasing worldwide. With this growing concern, the identification of clinical symptoms in high risk populations, such as those with a family history of diabetes, is becoming increasingly important.Objectives: This study aimed to determine the use of clinical symptoms and history as a screening tool for diabetes mellitus (DM) in a population with a family history of Type 2 Diabetes Mellitus (T2DM).Methods: The design of this research was a cross sectional study. The subjects of this study were a sample population with family history of T2DM living in Kasihan and Sewon District of Bantul Regency. Data were collected through interviews with questionnaires, anthropometric measurements, total cholesterol tests, triglycerides and fasting blood glucose tests. Data analysis used univariate, bivariate and multivariate analyses. For screening purposes, validity was performed against risk factors with fasting blood glucose as a gold standard.Results: Prevalence of DM was 30.5%, and prediabetes 26.5%. Body Mass Index (BMI) prevalence =23 kg/m2 59.02%, hypertension 42.62%, physical inactivity 21.31%, and dyslipidemia 78.69%. Polyuria, polydipsia, and weight loss were significantly associated with T2DM. Birth history of weight =4 kg or Gestational Diabetes Mellitus (GDM) was a risk factor associated with T2DM incidence (p = 0.018; OR: 1.93; CI 95%: 1.12-3.34). The sensitivity of a combination of several factors, birth history of baby =4 kg or GDM with dyslipidemia (sensitivity 87.3% specificity 40.9%), birth history of weight =4 kg or GDM with dyslipidemia and hypertension (sensitivity 94.7% specificity 26.7%), combination of the five factors studied (sensitivity 92.3% specificity 50%). Combination of birth history of heavy baby =4kg or GDM and BMI = 23 kg/m2  and hypertension had a likelihood ratio of 9.Conclusions: This study determined the prevalence of T2DM in populations with a family history of diabetes is high, with birth history of weight = 4 kg or GDM as a factor associated with T2DM, and other clinical symptoms having a fairly high prevalence. Therefore, a comprehensive lifestyle change needs to be done.